Konsep Pengaturan Saksi Mahkota dalam Proses Peradilan: Suatu Perbandingan dalam Hukum Acara Pidana Indonesia dan Belanda - Danusubroto, Alexia Sonia; Nelson, Febby Mutiara (Faculty of Law, Andalas University, 2023)
Crown witnesses are witnesses who come from or are taken from one of the suspects or other defendants who jointly commit a criminal offence. In its application in criminal justice in Indonesia, the existence of crown witnesses is still a matter of debate between one another. This paper discusses the concept of crown witnesses in Indonesian criminal justice with perpetrator witnesses or better known as crown witnesses in Dutch criminal justice using the comparative law method. The similarities and differences that exist between the two legal systems are not intended to determine which legal system is better than the other, but are intended as a method to understand how the legal system in another country, namely the Netherlands. The results of the research show that crown witnesses and perpetrator witnesses generally have the same concept as each other, the regulation of crown witnesses is contained in SEMA Number 4 of 2011 which describes the determination of justice collaborators who are in the position of suspects not as the main perpetrators and the need for participation in the criminal act they are charged with. As for the regulation in the Netherlands, it is contained in the Dutch Criminal Code Procedure which is regulated in the terms crown witness and undertaking witness. There are several differences such as the determination of testimony by the prosecutor, the existence of an agreement before giving testimony in Dutch criminal justice, and the possibility of refusal to testify in Dutch criminal justice.